Roles of Polymer Layer in Enhanced Photovoltaic Performance of Perovskite Solar Cells via Interface Engineering. Issue 3 (21st December 2017) - Yang, Fengjiu; Lim, Hong En; Wang, Feijiu; Ozaki, Masashi; Shimazaki, Ai; Liu, Jiewei; Mohamed, Nur Baizura; Shinokita, Keisuke; Miyauchi, Yuhei; Wakamiya, Atsushi; Murata, Yasujiro; Matsuda, Kazunari
Abstract: Perovskite solar cells (PSCs) have attracted intensive attention as the most promising next‐generation photovoltaic technology because they both enable accelerated development of photovoltaic performance and are compatible with low‐cost fabrication methods. The strategy of interface engineering of the perovskite layer in PSCs is expected to result in further enhancement of the power conversion efficiency (PCE) of PSCs via minimizing the charge recombination loss. Here, a high current–voltage (stabilized power output) PCE of 20.4% (19.9%) in CH3 NH3 PbI3 PSCs under reverse scanning conditions is demonstrated by incorporating a solution‐processed polymer layer of poly(methyl methacrylate) (PMMA) between the perovskite photoactive layer and the hole transport layer. Moreover, steady‐state and time‐resolved photoluminescence spectroscopy and impedance spectroscopy are used to reveal the mechanism of the enhancement of the photovoltaic performance and its stability by the PMMA layer in a CH3 NH3 PbI3 PSC device. The morphology modification, surface passivation, and protection of the perovskite layer by the insulating PMMA layer substantially contribute to the enhancement of photovoltaic performance and its stability, despite a slight reduction of the charge extraction efficiency. The demonstrated high PCEs and insights obtained into the working mechanism of the PMMA layer pave the way for the industrial application of CH3 NH3 PbI3 PSCs. Abstract : Enhanced surface quality of perovskite photoactive layer is demonstrated by incorporation of the poly(methyl methacrylate) (PMMA) engineered passivating layer, which results in highly enhanced power conversion efficiency from 16.8 to 20.4% of standard and PMMA‐incorporated perovskite solar cells, respectively, and reveals the working mechanism of PMMA layer in the perovskite solar cell device.